2016
DOI: 10.1136/bmjopen-2015-010366
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity and sedentary time: cross-sectional and prospective associations with adiposity in the Millennium Cohort Study

Abstract: ObjectiveTo examine whether physical activity (PA) and sedentary time (ST) in primary school-aged children are associated with adiposity at the start of secondary school, and whether these associations differ by sex or ethnic group.DesignNationally representative prospective cohort study.SettingChildren born across the UK, between 2000 and 2002.Participants6497 singleton children.Outcome measuresMeasures of adiposity (body mass index (BMI), fat mass index (FMI) and fat free mass index (FFMI))—obtained at 7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 61 publications
1
42
0
2
Order By: Relevance
“…Two studies found that sedentary time predicted lower BMI and WC , even after adjustment of MVPA. In general, studies examining the prospective associations between sedentary time and adiposity reported no evidence for any association . Activity of at least moderate intensity was inversely associated with BMI and WC .…”
Section: Resultsmentioning
confidence: 94%
“…Two studies found that sedentary time predicted lower BMI and WC , even after adjustment of MVPA. In general, studies examining the prospective associations between sedentary time and adiposity reported no evidence for any association . Activity of at least moderate intensity was inversely associated with BMI and WC .…”
Section: Resultsmentioning
confidence: 94%
“…Isolated adherence to MVPA, screen time and sleep duration recommendations have been associated with lower adiposity indicators in children and adolescents [3, 5–10]. How combinations of these movements behaviors are associated with obesity is largely unknown as few studies have examined the influence of meeting specific movement behavior recommendation combinations and obesity, and only a subset have considered sleep duration as a health-related risk behavior in combined analyses [1118].…”
Section: Introductionmentioning
confidence: 99%
“…In children and adolescents, adiposity, cardiovascular biomarkers, bone health, physical fitness, quality of life, motor skills development, and psychological distress have been associated with physical activity (PA), measured either in terms of minutes dedicated to total, light, moderate, and vigorous intensities [1][2][3][4] or sedentary time. 1,5,6 Current Spanish PA guidelines recommend that children and youth should accumulate at least 60 minutes of moderate-tovigorous PA (MVPA) daily and reduce screen time to no more than 2 hours daily.…”
mentioning
confidence: 99%
“…1,5,6 Current Spanish PA guidelines recommend that children and youth should accumulate at least 60 minutes of moderate-tovigorous PA (MVPA) daily and reduce screen time to no more than 2 hours daily. 7 Nevertheless, Spanish children have PA habits that are far from fulfilling the recommendations.…”
mentioning
confidence: 99%